ANALISIS PERUBAHAN PENUTUPAN LAHAN MENGGUNAKAN CITRA SATELIT LANDSAT ETM7+ PADA KAWASAN TAMAN NASIONAL GUNUNG PALUNG DI KABUPATEN KAYONG UTARA PROVINSI KALIMANTAN BARAT - Tricahyono, Kelik; Riyono, Joko Nugroho; Latifah, Siti (JURNAL HUTAN LESTARI, 2016)
Gunung Palung National Park has a very important role and a very significant function. Either ecological or conservation for the harborage against plasma nutfah resources of biodiversity and ecosystems which exist in Indonesia needs to manned and managed properly. Considering the importance of the role and functions of Gunung Palung National Park so its management needs to be supported by data and information that is complete, valid and actual. This research aimed access changes in land cover in Gunung Palung National Park residing in the district of North Kayong West Kalimantan Province between 2005 and 2012. The methodology used this research was supervised classification with Maximum Likelihood and visual, ground check spatial data analysis by using overlay for both data landsatETM7+image interpretation coverage on 2005 and data landsat ETM7+image interpretation coverage on 2012. The  research shows land cover on GunungPalung National Park residing in the district of North Kayong in 2012 was dominated by the Primary Swamp Forest of ± 39,27%, Primary Dryland Forest of ± 27,08% and Secondary Swamp Forest of ± 17,12%. Where as most small land cover is Grassland of ± 0,01%. The  biggest changed land cover occur in the Secondary Dryland Forests which decrease of ± 693,44 ha. The most significant changes when compared with the situation in 2005 is the Dryland Agriculture interference Bush that increased by ± 190,69%. Deforestation occurring is ± 1.122,21 ha (±160,32 ha/year), the degradation is ± 100,19 ha (±14.31 ha/year) as well as reforestation is ± 4.69 ha (± 0,67 ha/year). Keywords : Land cover changed, geographic information system, deforestation, degradation.If Full Text Pdf error, please use the link to acces : https://drive.google.com/file/d/0B2fYVAKSai7wUHY0UXNEcWNhRkk/view